(untitled) (Cardiovascular Journal, 2015)
Mitral stenosis (MS) is a still frequently encountered in India and Bangladesh. Untreated MS contributes to the morbidity and mortality. Balloon mitral Valvotomy is effective and commonly used for relief of obstruction in symptomatic patients. The case selection is guided by clinical characteristics and imaging. Echocardiography is the most important imaging modality to assess severity of obstruction its hemodynamic consequences as well as valve morphology. Transthoracic two dimensional echocardiography is usually sufficient to provide the desired information. Trans esophageal echocardiography is used when the valve cannot be adequately assessed by trans thoracic echocardiography and to exclude intracardiac thrombi prior to intervention. Three dimensional transthoracic and trans esophageal echocardiographic assessment provides more elaborate physiological and morphological information. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22261 Cardiovasc. j. 2015; 7(2): 128-136